Analyzing Cognitive Function in CLIL: Narratives of ESL Students in a Japanese-English Bilingual Mathematics Class of the International Baccalaureate Diploma Program - TAKAHASHI, Seiji; YOKOMATSU, Ayami; KIMURA, Mitsuhiro (The Journal of Japanese Society for Global Social and Cultural Studies, 2023)
This study explores the challenges and learning experiences of eight English learners in a bilingual CLIL trigonometry class, part of the International Baccalaureate Diploma program in a Japanese high school.Using the Cognitive Discourse Functions framework, students' spontaneous speech during reciprocal peer tutoring was classified and quantitatively analyzed to examine language use patterns. Furthermore, interviews with two participants provided insights into their self-analysis of learning English and math simultaneously in the course. Findings indicate that while students made efforts to enhance English intelligibility for peers, English usage declined during complex tasks.The interviews highlighted a conscious effort in assessing and optimizing their bilingual learning approach, illuminating the intricate balance between language acquisition and subject mastery in a bilingualeducational setting.